Implications of the use of podcast in the development of listening skills at a university level - Cárdenas Sánchez, Silva Elizabeth; Galimberti, Jessica Valentina (Machala : Editorial UTMACH, 2020)
A second or foreign language acquisition is a process in which learners develop and enhance different skills such as listening. However, students still struggle to comprehend L2. For instance, when a trainee works on a language proficiency, English listening material such as audios/videos and different pronunciations or sounds is difficult to analyze. Therefore, researchers have been investigating about techniques that work in classes and they found out that podcasting is increasingly being exploited by language teachers as a new popular and dynamic method to inspire learning inside and outside the traditional classroom (Stanley, 2006). This paper deals with student’s listening difficulties, podcasts’ technique and suggestions to be implemented in other settings.
Keywords: PODCAST; SLA; LISTENING COMPREHENSION; MOTIVATION